(Re)-writing the "New Society": A Multimodal Analysis of Marcos' Presidencies in Two Revisions of Philippines: Our Land and Heritage - Rodriguez, Maxine Rafaella C. (Journal of English Studies and Comparative Literature, 2020)
-